Technologies enabling rapid crop improvements for sustainable agriculture: example pennycress (Thlaspi arvense L.). Issue 2 (21st May 2021) - Marks, M. David; Chopra, Ratan; Sedbrook, John C.
Abstract : Growing concerns over food insecurity and ecosystems health related to population growth and climate change have challenged scientists to develop new crops, employing revolutionary technologies in combination with traditional methods. In this review, we discuss the domestication of the oilseed-producing cover crop pennycress, which along with the development of other new crops and improvements to farming practices can provide sustainable solutions to address malnutrition and environmental impacts of production agriculture. We highlight some of the new technologies such as bioinformatics-enabled next-generation sequencing and CRISPR genome editing in combination with traditional mutation breeding that has accelerated pennycress development as a new crop and a potential model system. Furthermore, we provide a brief overview of the technologies that can be integrated for improving pennycress and other crops and the status of pennycress development using these technologies.